Pengaruh Digital Marketing, Brand Awareness, dan Brand Image terhadap Minat Beli Ayam Asap Madu Pontianak - Imam Syafri; Yuni Firayanti; Marhamah Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to identify and analyze the influence of digital marketing, brand awareness, and brand image on the purchase intention of consumers of Ayam Asap Madu Pontianak. The research method used is a quantitative method with an associative approach. The population of this study consists of all consumers of Ayam Asap Madu Pontianak, with a total sample of 110 respondents. Data were collected through the distribution of questionnaires using a Likert scale of 1–5. The data analysis technique used is multiple linear regression analysis with the assistance of SPSS version 26, supplemented by classical assumption tests (normality, multicollinearity, and heteroscedasticity) and hypothesis testing through partial (t) and simultaneous (F) tests. The results of the study indicate that: (1) digital marketing has no significant influence on purchase intention with a tcount value of 1.622 < ttable 1.982 and a significance value of 0.108 > 0.05; (2) brand awareness has a positive and significant influence on purchase intention with a tcount value of 3.634 > ttable 1.982 and a significance value of 0.000 < 0.05; (3) brand image does not have a significant influence on purchase intention with a tcount value of 0.482 < ttable 1.982 and a significance value of 0.630 > 0.05; (4) simultaneously, digital marketing, brand awareness, and brand image have a significant influence on purchase intention with an Fcount of 5.992 > Ftable 3.08 and a significance value of 0.001 < 0.05. The regression equation obtained is Y = 11.104 + 0.214X1 + 0.539X2 + 0.082X3. The conclusion of this study is that, partially, only brand awareness has a significant influence on purchase intention, while digital marketing and brand image do not have a significant influence; however, simultaneously the three variables have a significant influence on the purchase intention of consumers of Ayam Asap Madu Pontianak.